Sistem Pelayanan Cuti Berbasis Web di Kantor Pelayanan Perbendaharaan Negara (KPPN) Lhokseumawe - Rozzi Kesuma Dinata, Erna (Jurnal Elektro dan Informatika, 2021)
In this era of globalization, information technology has become a basic tool needed by every existing company. By usinginformation technology, the accuracy and speed of data access will be easier to run. The Lhokseumawe State TreasuryService Office (KPPN) is a government office engaged in distributing funds from the state treasury to several work unitsunder other ministries/agencies or under the ministry of finance itself. The process of managing leave at theLhokseumawe State Treasury Service Office (KPPN) is currently still being done manually. The leave managementprocess has several weaknesses. Employees cannot find out the rest of their personal leave rights and take leave directlyby coworkers, so employees cannot carry out leave management properly. The leadership also has not been able to makeleave decisions based on the principle of equal distribution of employee leave rights. Another weakness is the process ofmanaging employee leave is less effective and efficient. In solving these problems, in this study the authors designed asystem using Unifield Modeling Language (UML), Personal Home Page (PHP) and using MySQL database. With theleave service system at the Lhokseumawe State Treasury Service Office (KPPN), employees will be able to more easilyaccess leave issues.